PENGARUH PENERAPAN PERAN TOTAL QUALITY MANAGEMENT TERHADAP KUALITAS SUMBERDAYA MANUSIA (Studi Kasus pada PT. BFI Finance Tbk. ) - Zusrony, Edwin (Universitas Muhammadiyah Surakarta, 2013)
This study aimed to determine the role of TQM in influencing the quality of HRemployees of PT. BFI Finance Tbk. Solo Branch. The population in this study were all employees,while the total study sample of 40 people and using the technique of saturated samples. In thisstudy using multiple linear regression method. Based on the results of studies using multipleregression analysis linieer known that the variable role of employee and organizational aspectshave a significant influence on the variable quality of human resources. While the dominantvariable in the study is the role of the employee variable, it can be seen from the magnitude of thebeta coefficient greater than the other independent variables.